Fiber alignment and mode-mixity effects on fracture behavior of CNF/epoxy nanocomposite adhesive joints. (December 2022) - Chanda, Amit; Sinha, Sujeet K.; Datla, Naresh V.
Abstract: In this study, the effect of carbon nanofiber (CNF) alignment was investigated on the enhancement of mixed mode fracture toughness of CNF/epoxy nanocomposite adhesive joints. CNFs were aligned in through-thickness direction inside epoxy using AC electric field. Asymmetric double cantilever beam (ADCB), Double cantilever beam (DCB), and end notched flexure (ENF) specimens were fabricated with pure epoxy, random, and aligned CNF/epoxy to investigate the mixed mode, mode-I, mode-II fracture response, respectively. Mixed mode and mode-II fracture toughness of 0.8 wt% aligned CNF/epoxy increased by 20% and 31.5%, respectively, compared to neat epoxy specimens ( G m, c = 960 ± 100 J/m 2, G I I C = 2772 ± 116 J/m 2 ). The mode-I fracture toughness of 0.8 wt% aligned CNF/epoxy was also increased by 195%, compared to the neat epoxy specimens ( G I C = 300 ± 31 J/m 2 ). Scanning electron micrograph analysis of fracture surfaces revealed that CNF pull-out, debonding and plastic void growth of epoxy are the key toughening mechanisms for all modes of fracture. These mechanisms were not so prevalent in the case of mixed mode and mode II fracture. Numerical modeling of all joints conducted using cohesive zone modeling matched satisfactorily with experimental findings. Highlights: Studied CNF alignment effect on mixed mode, mode-I and II fracture behavior. Observed enhanced fracture toughness ( G c ) with CNF concentration and alignment. G c enhancement is more prevalent in mode-I compared to mixed mode and mode-II. CNF pull-out, debonding and plastic void growth were found as toughening mechanisms. Numerically obtained load-displacement responses matched with experimental findings.